PENGARUH MODEL REALISTIC MATHEMATIC EDUCATION (RME) BERBANTUAN MEDIA KULINER SASAK TERHADAP HASIL BELAJAR MATEMATIKA - Huurun Iin Sakila; Moh. Irawan Zain; Hikmah Ramdhani Putri (PT. Hasba Edukasi Mandiri, 2025)
The effect of realistic mathematics education (RME) Model assisted by sasak culinary media on the Mathematics learning outcomes. The low level of students’ learning outcomes can be seen from the results of the 2022 PISA survey, which indicate scores significantly below the average of other participating countries, particularly in mathematical literacy. This study aims to determine the effect of applying the Realistic Mathematics Education (RME) model assisted by Sasak culinary media on the mathematics learning outcomes of fourth-grade students at SDN 13 Ampenan. This research employed a quantitative approach using a Quasi-Experimental Design with a Nonequivalent Control Group Design type. The samples were selected using purposive sampling, with class IV-C serving as the experimental group, which was taught using the RME model assisted by Sasak culinary media, and class IV-D serving as the control group, which was taught using a conventional learning model. The data collection instruments consisted of observation sheets and learning achievement tests that had been tested for validity and reliability. The data were analyzed using normality tests, homogeneity tests, independent t-tests, and N-Gain tests. The results showed a more significant improvement in learning outcomes in the experimental class (mean post-test score of 73.8) compared to the control class (mean post-test score of 60.4). The hypothesis test using the independent t-test showed a significance value (2-tailed) of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The N-Gain test result of 0.49 fell into the moderate category. Therefore, it can be concluded that the RME model assisted by Sasak culinary media has a positive effect on students’ mathematics learning outcomes.